The Measuring Ammonia in Nature (MAN) network in the Netherlands - D. E. Lolkema; H. Noordijk; A. P. Stolk; R. Hoogerbrugge; M. C. van Zanten; W. A. J. van Pul (Biogeosciences, 2015)
Since 2005 the Measuring Ammonia in Nature (MAN) network monitors atmospheric ammonia concentrations in nature reserve areas in the Netherlands (http://man.rivm.nl). The main aim of the network is to monitor national trends, to assess regional deviations and to validate model calculations. Measurements are performed with commercial passive samplers, calibrated monthly against ammonia measurements of active sampling devices. The sampling is performed by an extensive group of local volunteers, which minimizes the cost and enables the use of local knowledge. We show the MAN network to be well capable of monitoring trends on national and local scales and providing data for more detailed local analyses. The quality of the network is such that trends over time for individual MAN areas can be detected on the order of 3 % per year for time series of 6–9 years.